Respuestas

  • Usuario de Brainly
2013-02-21T16:32:17+01:00

Te ayudaré con algunas :

h) -2x +5 = (x+3)/5

       5*(-2x +5) = x+3

      -10x +25 = x+3

       -10x -x = 3 -25

          -11x = -22

            11x = 22

                  x = 22/11

                  x = 2

L) 1/(x-1) =  3/(2x+5)

       Multiplicamos en aspa :

   2x+5 = 3*(x-1)

    2x +5 = 3x -3

     2x -3x = -3-5

         -x = -8

         x = 8

o) (5x+2)/3 = (12x+4)/7

      Multiplicamos en aspa :

7*(5x+2) = 3*(12x+4)

35x +14= 36x + 12

 35x -36x = 12-14

        -x = -2

         x = 2

SaLuDos :)'